Ameloblastin in Hertwig’s Epithelial Root Sheath Regulates Tooth Root Formation and Development - Hirose, Naoto (Public Library of Science, 2013)
Tooth root formation begins after the completion of crown morphogenesis. At the end edge of the tooth crown, inner and outer enamel epithelia form Hertwig’s epithelial root sheath (HERS). HERS extends along with dental follicular tissue for root formation. Ameloblastin (AMBN) is an enamel matrix protein secreted by ameloblasts and HERS derived cells. A number of enamel proteins are eliminated in root formation, except for AMBN. AMBN may be related to tooth root formation; however, its role in this process remains unclear. In this study, we found AMBN in the basal portion of HERS of lower first molar in mice, but not at the tip. We designed and synthesized small interfering RNA (siRNA) targeting AMBN based on the mouse sequence. When AMBN siRNA was injected into a prospective mandibular first molar of postnatal day 10 mice, the root became shorter 10 days later. Furthermore, HERS in these mice revealed a multilayered appearance and 5-bromo-2′-deoxyuridine (BrdU) positive cells increased in the outer layers. In vitro experiments, when cells were compared with and without transiently expressing AMBN mRNA, expression of growth suppressor genes such as p21(Cip1) and p27(Kip1) was enhanced without AMBN and BrdU incorporation increased. Thus, AMBN may regulate differentiation state of HERS derived cells. Moreover, our results suggest that the expression of AMBN in HERS functions as a trigger for normal root formation.